Makna Pendhapa Ageng Mangkunegaran Sebagai Bangunan Adat Jawa - Adisukma, Wisnu (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2013)
This article analized about themeaning of javanesse building which is represented byPendhapa Ageng Mangkunegaran. Pendhapa Ageng Mangkunegaran in cultural frame is not onlybuilding for conference or ceremony but also has wider role. Although, this building as materialbut still has psychological role meaning. Explicit or implicit meaning in building and ornamentform at Pendhapa Ageng Mangkunegaran has particular meaning, massage and role. As,particular system, the myth is built by second meaning system. In this myth, also signified thathas several signifier.